2021
DOI: 10.54753/cedamaz.v11i2.1177
|View full text |Cite
|
Sign up to set email alerts
|

Situación actual y predicción del ruido vehicular en la zona urbana de la ciudad de Loja (Ecuador)

Abstract: La ciudad de Loja está siendo afectada por el incremento de su parque automotor, y como consecuencia de ello, por un mayor ruido. Este estudio tuvo como objetivo analizar la situación actual y futura del ruido generada por el parque automotor de la zona urbana de la ciudad de Loja. Para ello, se recopilaron datos de presión sonora de investigaciones previas y mediciones en distintas avenidas y calles de la ciudad, desde el año 2007 al 2019 y en tres horarios: 07:00-09:00, 11:00-13:00 y 17:00-19:00. La situació… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…(7) Descriptive statistical analysis, based on frequencies, and inferential analysis were used to determine the relevance of each factor. (8) The results revealed that 58,2 % of the respondents indicated that vehicular noise did not affect them, while others considered that it did have a negative impact, highlighting lack of concentration and demotivation as the highest priority problems. In addition, the effects of anxiety, fatigue, and aggression were observed.…”
Section: Introductionmentioning
confidence: 95%
“…(7) Descriptive statistical analysis, based on frequencies, and inferential analysis were used to determine the relevance of each factor. (8) The results revealed that 58,2 % of the respondents indicated that vehicular noise did not affect them, while others considered that it did have a negative impact, highlighting lack of concentration and demotivation as the highest priority problems. In addition, the effects of anxiety, fatigue, and aggression were observed.…”
Section: Introductionmentioning
confidence: 95%